Post-tracheostomy tracheoinnominate fistula: endovascular treatment - Lisieux Eyer de Jesus; Eduardo Wagner Guimarães Marques da Silva; Marcos Balieiro; Karen Feldman; Samuel Dekermacher (Revista Paulista de Pediatria, 2021)
ABSTRACT Objective: Tracheoinnominate fistula (TIF) is a rare and frequently lethal complication of tracheostomies. Immediate bleeding control and surgical treatment are essential to avoid death. This report describes the successful endovascular treatment of TIF in a preschooler and reviews the literature concerning epidemiology, diagnosis, prophylaxis, and treatment of TIF in pediatric patients. Case description: A tracheostomized neurologically impaired bed-ridden three-year-old girl was admitted to treat an episode of tracheitis. Tracheostomy had been performed two years before. The child used a plastic cuffed tube continually inflated at low pressure. The patient presented two self-limited bleeding episodes through the tracheostomy in a 48h interval. A new episode was suggestive of arterial bleeding, immediately leading to a provisional diagnosis of TIF, which was confirmed by angiotomography, affecting the bifurcation of the innominate artery and the right tracheal wall. The patient was immediately treated by the endovascular placement of polytetrafluoroethylene (PTFE)/nitinol stents in Y configuration. No recurrent TIF, neurological problems, or right arm ischemia have been detected in the follow-up. Comments: TIF must be suspected after any significant bleeding from the tracheostoma. Endovascular techniques may provide rapid bleeding control with low morbidity, but they are limited to a few case reports in pediatric patients, all of them addressing adolescents. Long-term follow-up is needed to detect whether stent-related vascular complications will occur with growth.